Inhaled short acting ß agonist use in COPD and the risk of acute myocardial infarction - Suissa, S (BMJ Group, 2003)
Background: A recent study found that short acting ß agonists used in the treatment of asthma and chronic obstructive pulmonary disease (COPD) may increase the risk of acute myocardial infarction. We investigated this hypothesis in patients with COPD already at high risk of cardiac disease. Methods: The Saskatchewan Health Services databases were used to form a population based cohort of all patients newly diagnosed with COPD over the age of 55 years identified between 1980 and 1997. All subjects were followed up until 1999, death, or the first occurrence of acute myocardial infarction. Those with a first acute myocardial infarction, fatal or non-fatal, were matched on calendar time and age with cohort members. Results: The cohort consisted of 12 090 subjects including 1127 cases with fatal or non-fatal acute myocardial infarction. The adjusted rate ratio for current use of inhaled ß agonists was 1.12 (95% confidence interval (CI) 0.95 to 1.33), and for first time use it was 1.02 (95% CI 0.52 to 2.00). There was also no significant increase in risk when the analysis was restricted to subjects with cardiac risk factors such as hypertension and diabetes, or to subjects not having been prescribed ß blocker medications. Conclusion: Short acting inhaled ß agonist use among patients with COPD does not appear to increase the risk of fatal or non-fatal acute myocardial infarction.